No platform: a history of anti-fascism, universities and the limits of free speech - Smith, Evan (Routledge studies in fascism and the far right, 2020)
'No platform' in historical and contemporary context -- Fascism, anti-fascism and free speech before 'no platform' -- The student movement and the prelude to 'no platform' -- The National Union of Students and 'no platform' in the 1970s -- Expanding 'no platform' in the 1980s -- Hard right politicians and student protests at universities in the 1980s -- Into the twenty first century -- Why 'no platform' matters.